Effects of Sex Class, a Combined Androgen and Estrogen Implant, and Pasture Supplementation on Growth and Carcass Performance and Meat Quality of Zebu-Type Grass-Fed Cattle - Nelson Huerta-Leidenz; Nancy Jerez-Timaure; Jhones Onorino Sarturi; Mindy M. Brashears; Markus F. Miller; Alexis Moya; Susmira Godoy (Animals, 2021)
Forty-seven Zebu calves were used to determine the effects of class (bull or steer), supplementation (SUPPL, a poultry litter-based supplement or mineral supplementation), and implant (20 mg estradiol combined with 120 mg of trenbolone acetate or no implant) on growth and carcass performance and beef eating quality. The average daily gain (ADG) of implanted cattle significantly increased for steers, but not for bulls. The SUPPL treatment increased ADG by 8.63% from day 0 to end, and shortened in 73.3 d the time to reach 480 kg BW (p < 0.01). Compared to bulls, the steer carcasses exhibited more desirable maturity and finish scores, thicker back fat (p < 0.05), and yielded greater (p < 0.01) percentages of high-value boneless subprimals (HVBLS) (+1.64%) and total cuts (1.35%). The SUPPL bulls dressed 2.63 and 1.63% greater than non-supplemented bulls and SUPPL steers, respectively (p < 0.05). Meat sensory quality was subtly affected (p < 0.05) by sex class or supplementation. The implant did not affect (p > 0.05) shear force or sensory ratings. The supplementation improved key growth performance traits while it adversely affected tenderness-related sensory traits. The implant enhanced the rate of gain of steers only, without improving cut-out yields or inducing adverse effects on palatability traits in both steers and bulls.